Ordered La0.7Sr0.3MnO3 nanohole arrays fabricated on a nanoporous alumina template by pulsed laser ablation - Kumaresavanji, M. (2016)
Highly ordered nanohole arrays of [Formula: see text] manganite have been synthesized using pulsed laser deposition on nanoporous alumina template. Their structure and phase formation were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), energy dispersive x-ray spectroscopy (EDX) and x-ray diffraction (XRD). The magnetic measurements were performed with respect to temperature and field and exhibit a ferromagnetic to paramagnetic transition at 284 K. In addition, the temperature dependence of electrical resistance was measured at different magnetic fields and an insulating phase throughout all the temperatures was observed. The low temperature ferromagnetic insulating state is discussed by the presence of a canted ferromagnetic state induced by the nanoholes. The present work shows the feasibility of combining both the nanoporous alumina template and pulsed laser ablation for the fabrication of perovskite manganite nanohole arrays which can also be extended to fabricate other multicomponent oxide nanohole materials.